Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Let's solve the equation step by step to find the correct value of [tex]\( x \)[/tex]:
The given equation is:
[tex]\[ 4x + x - 15 + 3 - 8x = 13 \][/tex]
1. Combine like terms:
First, we group the terms involving [tex]\( x \)[/tex] and the constants separately:
[tex]\[ 4x + x - 8x - 15 + 3 = 13 \][/tex]
Simplify the [tex]\( x \)[/tex]-terms:
[tex]\[ (4x + x - 8x) + (-15 + 3) = 13 \][/tex]
Combine the coefficients of [tex]\( x \)[/tex]:
[tex]\[ -3x \][/tex]
Combine the constants:
[tex]\[ -15 + 3 = -12 \][/tex]
So the equation simplifies to:
[tex]\[ -3x - 12 = 13 \][/tex]
2. Isolate the term with [tex]\( x \)[/tex]:
Add 12 to both sides of the equation to isolate terms involving [tex]\( x \)[/tex]:
[tex]\[ -3x - 12 + 12 = 13 + 12 \][/tex]
This simplifies to:
[tex]\[ -3x = 25 \][/tex]
3. Solve for [tex]\( x \)[/tex]:
Divide both sides by -3 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{25}{-3} \][/tex]
This simplifies to:
[tex]\[ x = -\frac{25}{3} \][/tex]
Therefore, the value of [tex]\( x \)[/tex] is:
[tex]\[ x = -\frac{25}{3} \][/tex]
The correct answer is:
[tex]\[ \boxed{D} \][/tex]
The given equation is:
[tex]\[ 4x + x - 15 + 3 - 8x = 13 \][/tex]
1. Combine like terms:
First, we group the terms involving [tex]\( x \)[/tex] and the constants separately:
[tex]\[ 4x + x - 8x - 15 + 3 = 13 \][/tex]
Simplify the [tex]\( x \)[/tex]-terms:
[tex]\[ (4x + x - 8x) + (-15 + 3) = 13 \][/tex]
Combine the coefficients of [tex]\( x \)[/tex]:
[tex]\[ -3x \][/tex]
Combine the constants:
[tex]\[ -15 + 3 = -12 \][/tex]
So the equation simplifies to:
[tex]\[ -3x - 12 = 13 \][/tex]
2. Isolate the term with [tex]\( x \)[/tex]:
Add 12 to both sides of the equation to isolate terms involving [tex]\( x \)[/tex]:
[tex]\[ -3x - 12 + 12 = 13 + 12 \][/tex]
This simplifies to:
[tex]\[ -3x = 25 \][/tex]
3. Solve for [tex]\( x \)[/tex]:
Divide both sides by -3 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{25}{-3} \][/tex]
This simplifies to:
[tex]\[ x = -\frac{25}{3} \][/tex]
Therefore, the value of [tex]\( x \)[/tex] is:
[tex]\[ x = -\frac{25}{3} \][/tex]
The correct answer is:
[tex]\[ \boxed{D} \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.